Employer concentration and wages for specialized workers - Anna Thoresson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
This paper studies how wages respond to a sudden change in employer concentration. It exploits a reform that deregulated the Swedish pharmacy market, which until 2009 was a monopoly. The reform involved a substantial increase in the number of employers on the pharmacy labor market. However, the change in employer concentration was not geographically uniform: certain areas experienced large changes while others were largely unaffected. Exploiting this geographical variation, elasticities of wages with respect to labor market concentration are estimated to be between -0.02 and -0.05. The empirical approach relies only on the variation in concentration controlled by the policymaker to remedy the concern that actual labor market concentration is endogenous. The positive wage effects from reduced labor market concentration are found to be most prevalent for stayers, rather than new hires, as well as those with more industry experience and longer tenure. Overall, the paper adds to a growing literature that finds that market concentration matters for workers' wages, in a context where labor is highly industry-specific.
Keywords: J31; J42; J45; 330; Wages; Competition; Market concentration